Rev-erb-α regulates atrophy-related genes to control skeletal muscle mass. Issue 1 (December 2017) - Mayeuf-Louchart, Alicia; Thorel, Quentin; Delhaye, Stéphane; Beauchamp, Justine; Duhem, Christian; Danckaert, Anne; Lancel, Steve; Pourcet, Benoit; Woldt, Estelle; Boulinguiez, Alexis; Ferri, Lise; Zecchin, Mathilde; et al.
Abstract The nuclear receptor Rev-erb-α modulates hepatic lipid and glucose metabolism, adipogenesis and thermogenesis. We have previously demonstrated that Rev-erb-α is also an important regulator of skeletal muscle mitochondrial biogenesis and function, and autophagy. As such, Rev-erb-α over-expression in skeletal muscle or its pharmacological activation improved mitochondrial respiration and enhanced exercise capacity. Here, in gain- and loss-of function studies, we show that Rev-erb-α also controls muscle mass. Rev-erb-α-deficiency in skeletal muscle leads to increased expression of the atrophy-related genes (atrogenes), associated with reduced muscle mass and decreased fiber size. By contrast, in vivo andin vitro Rev-erb-α over-expression results in reduced atrogenes expression and increased fiber size. Finally, Rev-erb-α pharmacological activation blocks dexamethasone-induced upregulation of atrogenes and muscle atrophy. This study identifies Rev-erb-α as a promising pharmacological target to preserve muscle mass.